Chrm3 protects against acinar cell necrosis by stabilizing caspase‐8 expression in severe acute pancreatitis mice model. Issue 3 (6th November 2019) - Huang, Ning; Murtaza, Ghulam; Wang, Lujing; Luan, Jing; Wang, Xinlei; Sun, Yumiao; Wu, Xing; Tao, Yuxi; Shi, Shuoxi; Cao, Peihua; Qiao, Yu; Han, Dong; et al.
Abstract: Acinar cells in acute pancreatitis (AP) die through apoptosis and necrosis, the impacts of which are quite different. Early clinical interference strategies on preventing the progress of AP to severe acute pancreatitis (SAP) are the elimination of inflammation response and inhibition of necrosis. Muscarinic acetylcholine receptor M3 was encoded by Chrm3 gene. It is one of the best‐characterized receptors of pancreatic β cells and regulates insulin secretion, but its function in AP remains unclear. In this study, we explored the function of Chrm3 gene in the regulation of cell death in l ‐arginine‐induced SAP animal models. We found that Chrm3 was upregulated in pancreatitis, and we further confirmed the localization of Chrm3 resided in both pancreatic islets and acinar cell membranes. The reduction of Chrm3 decreased the pathological lesion of SAP and reduced amylase activities in serum. Consistently, Chrm3 can suppress acinar cells necrosis markedly, but has no effect on regulating apoptosis after l ‐arginine treatment. It was shown that Chrm3 attenuated acinar cells necrosis at least in part by stabilizing caspase‐8. Thus, this study indicates that Chrm3 is critical participants in SAP, and regulation of Chrm3 expression might be a useful therapeutic strategy for preventing pathologic necrosis. Abstract : The localization of Chrm3 resided in both pancreatic islets and acinar cell membranes. The major findings of this study are that Chrm3 could regulate pancreatic acinar cell death and that loss of Chrm3 could prevent necrosis by regulating caspase‐8 during l ‐arginine‐induced severe acute pancreatitis.